Let's talk about it: conversations in advance care planning. Issue 1 (1st June 2011) - Beavan, J; Fowler, C; Russell, S
Abstract : This workshop is based on Chapter 23 in Thomas and Lobo (2010) 1 where communication skills are seen as integral to delivering advance care planning (ACP). It reflects the need to teach the principles of ACP alongside communication skills. It recognises that to teach these in isolation may lead to a lack of confidence in the professional engaging patients in discussions around end of life care issues. This workshop draws on models of communication that can lend structure, such as SPIKES, PREPARED, SAGE & THYME and the Calgary-Cambridge model of the consultation. To demonstrate how theory moves into practice, relevant scenarios have been identified to illustrate how they may be used. The theory outlined in Chapter 23 has been taken into the workplace to inform the model of education used in delivering ACP. This work is innovative in understanding the relationship between communication skills and effective ACP and has been put into practice in education development. The workshop will consider the key points of an ACP process. Role played scenarios will be used to engage participants in an interactive process that allows specific communication skills to be demonstrated and reflected upon in the context of ACP.